Analisis Keterampilan Metakognitif Peserta Didik Menggunakan Model Inkuiri Terbimbing pada Materi Laju Reaksi Berbasis Pembelajaran Daring - Rizza Danila; Rudiana Agustini (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to analyze students' metacognitive skills using guided Inquiry models of reaction rate material based on online learning. The research subjects were students of 2nd grade IPA 2 SMAN 1 Driyorejo in the academic year 2020/2021 totaling 33 students. The study used a quantitative descriptive method with One-Group Pretest-Posttest Design and techniques of data collections used test and questionnaire. The data analysis techniques used in this research was descriptive statistical analysis and inferential analysis. The results of this study showed an increase in the metacognitive skills of students using the guided Inquiry model on the reaction rate material based on online learning which could be seen from the results of the posttest scores being better than the pretest with the n-gain value of planning skills of 0.63 in medium category; n-gain of monitoring skills of 0.92 in high category; n-gain of evaluating skills of 0.65 in medium category. Based on inferential analysis using the Wilcoxon signed ranks test, it showed the significance of the indicators planning skill, monitoring skills, and evaluating skills with a value of 0,000 which 0,000 <0.05, means that the hypothesis is accepted. This indicated that learning using guided inquiry model had a significant effect on students’s metacognitive skills in the reaction rate material based on online learning.